The Importance of the Autopsy in Medicine: Perspectives of Pathology Colleagues - Louis Maximilian Buja MD; Rolf F. Barth MD; Gerhard R. Krueger MD; Sergey V. Brodsky MD, PhD; Robert L. Hunter MD, PhD (Elsevier, 2019)
This article presents a perspective on the importance of the autopsy in medical practice and science based on experiences of the authors as physician-scientists involved in autopsy practice. Our perspectives are presented on the seminal contributions of the autopsy in the areas of cardiovascular disease, including congenital heart disease, atherosclerosis, coronary artery disease, and myocardial infarction, and infectious disease, including tuberculosis and viral infections. On the positive side of the future of the autopsy, we discuss the tremendous opportunities for important research to be done by application of advanced molecular biological techniques to formalin-fixed, paraffin-embedded tissue blocks obtained at autopsy. We also note with concern the countervailing forces impacting the influence of pathology in education and clinical practice at our academic medical centers, which also present impediments to increasing autopsy rates. Our challenge as academic pathologists, whose careers have been molded by involvement in the autopsy, is to counter these trends. The challenges are great but the benefits for medicine and society are enormous.